Beep, beep, vroom, vroom! - Murphy, Stuart J.; Demarest, Chris L. (New York : HarperCollins Publishers, 2000)
As Molly plays with her big brother's toy cars, readers will see and recognize patterns, an essential first step in learning to reason from the specific to the general.
Keywords: Children's stories